Effects of dietary Saccharomyces cerevisiae on growth, intestinal and liver health, intestinal microbiota and disease resistance of channel catfish (Ictalurus punctatus) - Rui Xia (Aquaculture Reports, 2022)
Probiotics are an eco-friendly alternative to antibiotics and play an important role in ensuring the sustainability of aquaculture. The aim of the present study was to investigate the effects of Saccharomyces cerevisiae on the growth, intestinal and liver health, intestinal microbiota, and disease resistance of channel catfish (Ictalurus punctatus). Channel catfish were randomly allotted into two treatments, control group (basal diet) and SCC group (basal diet with 2% Saccharomyces cerevisiae culture), and fed for 12 weeks. The results showed that the weight gain of SCC group was significantly increased (P < 0.05) and FCR was significantly decreased (P < 0.05) when compared with the control group. SCC diet significantly improved the intestinal structural integrity of channel catfish and increased the number of intestinal goblet cell. The expression of intestinal gene HIF1α was increased in SCC group, while the expressions of NF-κB in the intestine and liver were significantly decreased (P < 0.05). The relative abundance of Firmicutes tended to increase, while Proteobacteria had a tendency to decrease (0.20 > P > 0.05). In addition, the survival rate of channel catfish was significantly increased in SCC group after being challenged with mixture of A. veronii HM091 and A. hydrophila NJ-1. In conclusion, the supplementation of Saccharomyces cerevisiae culture improved the growth, intestinal and liver health and disease resistance of channel catfish.